A Simple Nematode Infection Model for Studying Candida albicans Pathogenesis. Issue 1 (25th September 2020) - Kim, Grace H.; Rosiana, Sierra; Kirienko, Natalia V.; Shapiro, Rebecca S.
Abstract: Candida albicans is an opportunistic fungal pathogen and a model organism to study fungal pathogenesis. It exists as a harmless commensal organism and member of the healthy human microbiome, but can cause life‐threatening mucosal and systemic infections. A model host to study C. albicans infection and pathogenesis is the nematode Caenorhabditis elegans . C. elegans is frequently used as a model host to study microbial‐host interactions because it can be infected by many human pathogens and there are also close morphological resemblances between the intestinal cells of C. elegans and mammals, where C. albicans infections can occur. This article outlines a detailed methodology for exploiting C. elegans as a host to study C. albicans infection, including a C. elegans egg preparation protocol and an agar‐based C. elegans killing protocol to monitor fungal virulence. These protocols can additionally be used to study C. albicans genetic mutants in order to further our understanding of the genes involved in pathogenesis and virulence in C. albicans and the mechanisms of host‐microbe interactions. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of Caenorhabditis elegans eggs Support Protocol 1 : Freezing and recovering Caenorhabditis elegans Support Protocol 2 : Making superfood agar and OP50 plates Basic Protocol 2 : Caenorhabditis elegans / Candida albicans agar killing assay Support Protocol 3 : Constructing a worm pick